2005
DOI: 10.1128/mcb.25.10.4129-4137.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Ciliary Rootlet Maintains Long-Term Stability of Sensory Cilia

Abstract: The striated ciliary rootlet is a prominent cytoskeleton originating from basal bodies of ciliated cells. Although a familiar structure in cell biology, its function has remained unresolved. In this study, we carried out targeted disruption in mice of the gene for rootletin, a component of the rootlet. In the mutant, ciliated cells are devoid of rootlets. Phototransduction and ciliary beating in sensory and motile cilia initially exhibit no apparent functional deficits. However, photoreceptors degenerate over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 29 publications
8
161
0
Order By: Relevance
“…Striated rootlets are also present in the spermatozoa of many invertebrates (e.g., Platyhelminthes; Justine, 1995), as well as in the spermatids of Postorchigenes (Platyhelminthes: Trematoda: Lecithodendriidae; Gracenea et al, 1997). Work by Yang et al (2002Yang et al ( , 2005 on striated rootlets of ciliated cells demonstrated that rootlets are critical structures for support of cilia and are composed of a large protein called rootletin. Although rootlets were not required for ciliary motility, their presence increased survival and enabled significantly more normal ciliated cells to withstand mechanical stress compared to mutant ciliated cells that lacked rootlets (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Striated rootlets are also present in the spermatozoa of many invertebrates (e.g., Platyhelminthes; Justine, 1995), as well as in the spermatids of Postorchigenes (Platyhelminthes: Trematoda: Lecithodendriidae; Gracenea et al, 1997). Work by Yang et al (2002Yang et al ( , 2005 on striated rootlets of ciliated cells demonstrated that rootlets are critical structures for support of cilia and are composed of a large protein called rootletin. Although rootlets were not required for ciliary motility, their presence increased survival and enabled significantly more normal ciliated cells to withstand mechanical stress compared to mutant ciliated cells that lacked rootlets (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Work by Yang et al (2002Yang et al ( , 2005 on striated rootlets of ciliated cells demonstrated that rootlets are critical structures for support of cilia and are composed of a large protein called rootletin. Although rootlets were not required for ciliary motility, their presence increased survival and enabled significantly more normal ciliated cells to withstand mechanical stress compared to mutant ciliated cells that lacked rootlets (Yang et al, 2005). In a spermatozoon, the rootlet may therefore act to stabilize the cell during periods of flagellar swimming.…”
Section: Discussionmentioning
confidence: 99%
“…C-Nap1 interacts with rootletin, a conserved component of the ciliary rootlet. The ciliary rootlet is a cytoskeletal structure found in many ciliated cells that originates from the basal body and extends proximally toward the nucleus, providing structural support for the cilium (Yang et al, 2005). Rootletin is, however, also found in cells devoid of a ciliary rootlet, forming fibers that emanate from the proximal ends of centrioles.…”
Section: Centrosome Duplicationmentioning
confidence: 99%
“…Striated rootlets are a general feature of ciliated cells and some are capable of calcium-dependent contraction [78]. Rootlet components include isoforms of centrin/caltractin, a calmodulin-related protein that regulates rootlet contractility [105,106], and rootletin, a large coiledcoil protein required to maintain mammalian sensory cilia [109,110]. Drosophila has genes encoding two centrin isoforms and a rootletin homolog.…”
Section: Chordotonal Organ Structure and Functionmentioning
confidence: 99%